2008
DOI: 10.1089/jwh.2007.0379
|View full text |Cite
|
Sign up to set email alerts
|

Lipid-Lowering Medication Use and Aggression Scores in Women: A Report from the NHLBI-Sponsored WISE Study

Abstract: Aim-The aim of this study was to examine the association between the use of lipid-lowering medication and aggressive responding, hostility, cynicism, and depression scores in women undergoing coronary angiography.Methods-The cohort included 498 women from the National Heart, Lung and Blood Institute (NHLBI)-sponsored Women's Ischemia Syndrome Evaluation (WISE) study. WISE is a four-center study of women with chest pain who underwent quantitative coronary angiography for suspected myocardial ischemia. The psych… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 55 publications
2
27
0
Order By: Relevance
“…In a study of 915 offenders in Canada, for example, diabetes was twice as prevalent as compared to the general population, was mostly undiagnosed or untreated at the time of offense, and was most frequent among violent and sex offenders whose victims were children (35). From a legal perspective, uncontrolled diabetes has historically been considered a “disease of the mind” and within the scope of the insanity defense (49), though the association between medical comorbidity severity and criminality or aggression has more recently been suggested in relation to epilepsy (50), dyslipidemia (51), and others, mostly in men. Missing from these studies is consideration of race/ethnicity, neighborhood, and socioeconomic status as confounders that likely contribute both to serious health disparities and CJ risk (52).…”
Section: Discussionmentioning
confidence: 99%
“…In a study of 915 offenders in Canada, for example, diabetes was twice as prevalent as compared to the general population, was mostly undiagnosed or untreated at the time of offense, and was most frequent among violent and sex offenders whose victims were children (35). From a legal perspective, uncontrolled diabetes has historically been considered a “disease of the mind” and within the scope of the insanity defense (49), though the association between medical comorbidity severity and criminality or aggression has more recently been suggested in relation to epilepsy (50), dyslipidemia (51), and others, mostly in men. Missing from these studies is consideration of race/ethnicity, neighborhood, and socioeconomic status as confounders that likely contribute both to serious health disparities and CJ risk (52).…”
Section: Discussionmentioning
confidence: 99%
“…This might be a possible mechanism for statins to affect cognitive function, neurodegenerative disease, and various neurological disorders, such as stroke, epilepsy, depression, and central nervous system cancers [29]. A few studies have reported negative or inconclusive effects of statins on mood [30, 31]. One researcher even reported that lower serum cholesterol levels are associated with increased mortality from suicide [32].…”
Section: Discussionmentioning
confidence: 99%
“…Cholesterol was eluted in the retention time of 12.7 min. A mass spectrometer equipped with an atmosphere pressure chemical ionization (APCI) was used for the detection of cholesterol and their deuterium labeled internal standards (cholesterol-d 6 The fragmentation ion for cholesterol and its internal standard was selected on the basis of a collision spectrum (see Fig. 1).…”
Section: Analytical Methods For Determination Of Cholesterol In the Bmentioning
confidence: 99%
“…However, in 2012, the U.S. Food and Drug Administration (FDA) approved a safety warning on the cognitive side effects associated with statins [1]. Psychological adverse events may include behavioral alterations such as irritability, impulsiveness and hostility [2][3][4][5][6][7], depression [8], as well as cognitive and memory impairments [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%